Banks' trust in the EU macroprudential regulation - Matias Huhtilainen (Journal of Banking and Financial Economics (JBFE), 2019)
Prior studies suggest that regulatory uncertainty is potentially detrimental to the wider economic performance, to the effectiveness of regulatory measures and to the objective of harmonized rules and a level playing field across jurisdictions. This paper discusses on the applicability of banks' perceived trust as a method to evaluate the quality of the EU macroprudential regulation. Accordingly, the regulatory credibility, as opposed to regulatory uncertainty, is assumed to indicate consistent, predictable and solid regulatory and institutional environment. This paper argues that the perception of trust and the regulatory credibility are interrelated so that one cannot exist without the other. For the purpose of this study, a representative survey was conducted with Finnish banks and conglomerates. Although the respondents expressed, overall, slight trust in the ability of the renewed EU macroprudential regime to accomplish its intended objectives, definitive and direct conclusions are avoided. This is due to the several limitations of the survey and as such, the results are merely to provide context for the paper.
Keywords: G280; G210; K220; 330; CRD IV; Banking Union; Macroprudential Regulation; Systemic Stability; Trust